2010
DOI: 10.1111/j.1755-263x.2010.00105.x
|View full text |Cite
|
Sign up to set email alerts
|

Global patterns of marine turtle bycatch

Abstract: Fisheries bycatch is a primary driver of population declines in several species of marine megafauna (e.g., elasmobranchs, mammals, seabirds, turtles). Characterizing the global bycatch seascape using data on bycatch rates across fisheries is essential for highlighting conservation priorities. We compiled a comprehensive database of reported data on marine turtle bycatch in gillnet, longline, and trawl fisheries worldwide from 1990 to 2008. The total reported global marine turtle bycatch was ∼85,000 turtles, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
219
0
10

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 278 publications
(233 citation statements)
references
References 28 publications
4
219
0
10
Order By: Relevance
“…Using onboard observer data, Gardner et al (2008) found seasonal changes in catch distributions of loggerhead and leatherback turtles in the North Atlantic, with patterns of spatial clustering from July to October. Analysed on a global scale, Wallace et al (2010b) were able to highlight region− gear combinations requiring urgent action such as gillnets, longlines and trawls in the Mediterranean Sea and eastern Pacific Ocean. Generating such estimates of catch rates and spatial/temporal patterns for entanglement are not yet possible due to the lack of quantitative information.…”
Section: Differentiation From Bycatchmentioning
confidence: 99%
“…Using onboard observer data, Gardner et al (2008) found seasonal changes in catch distributions of loggerhead and leatherback turtles in the North Atlantic, with patterns of spatial clustering from July to October. Analysed on a global scale, Wallace et al (2010b) were able to highlight region− gear combinations requiring urgent action such as gillnets, longlines and trawls in the Mediterranean Sea and eastern Pacific Ocean. Generating such estimates of catch rates and spatial/temporal patterns for entanglement are not yet possible due to the lack of quantitative information.…”
Section: Differentiation From Bycatchmentioning
confidence: 99%
“…Fisheries bycatch is recognized as perhaps the most serious global threat to highly migratory, long-lived marine taxa including turtles (Wallace et al 2010a, birds (Croxall et al 2012, Lewison et al 2012, mammals (Read et al 2006), and sharks (Dulvy et al 2008). Marine megafauna species are susceptible to fisheries bycatch because they occupy broad geographic distributions across geopolitical boundaries and oceanographic regions that support both small-and large-scale fisheries, and because their life histories (e.g., delayed maturity, low reproductive rates) make them particularly sensitive to sources of mortality that affect late life stages (Crouse et al 1987, Heppell et al 2005.…”
Section: Introductionmentioning
confidence: 99%
“…Third, exploitation of productive species, such as tunas, at MSY is driving steep population declines and elevating the risk of extinction of some unmanaged and less productive bycatch species. Tuna fisheries are directly responsible for endangering a wide range of oceanic pelagic sharks, billfishes, seabirds, and turtles (26,27).…”
Section: Discussionmentioning
confidence: 99%